If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.3x + -0.7x + -19 = 1 Reorder the terms: -19 + 0.3x + -0.7x = 1 Combine like terms: 0.3x + -0.7x = -0.4x -19 + -0.4x = 1 Solving -19 + -0.4x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + -0.4x = 1 + 19 Combine like terms: -19 + 19 = 0 0 + -0.4x = 1 + 19 -0.4x = 1 + 19 Combine like terms: 1 + 19 = 20 -0.4x = 20 Divide each side by '-0.4'. x = -50 Simplifying x = -50
| 2.6=-0.2t | | m+12=26 | | 2(4c-1)-6=5c+4 | | 6-3(r+2)=5(r+3)+1 | | -1-1-1-1-1-1-1+6+1=23332 | | 5t-10=i+2 | | 3x-2+28+28=6x | | t+12=52 | | x-5/x+5=x-6/x-1 | | 3/4m=-27/12 | | 69-6x=21x+21 | | 8/7w=56 | | 13-(5m+4)=5+3m-12 | | 5+x/4=11 | | 9+8x-3=2(3x+8) | | 5h+7=5(h+2)-3 | | X(8x+11)=6x-5 | | X+5/6=-1/5 | | (4/15)-(1/6) | | Y=6*-2+6 | | 0.7/14 | | 2=9+x/7 | | 6/x+5=-15/x-2 | | 14/0.7 | | (x^7/4)-(4x^7/8)+4=0 | | x-115=125 | | z-2323233322=-23-2z | | log(5+r)=log(5s-2) | | x+23+3x=-11-3x-15 | | 2(m-1)=-4 | | 9+8-3=2(3+8) | | x^7/4-4x^7/8+4=0 |